(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Employee retention is one of the most important factors that an organization needs to consider when developing its strategies. Even though most of the organizations are now a days, found to be technology driven, yet human resources are required to run the technology. Retention of employees is emerging as the most important human resource management problems in IT companies. The IT Sector is committed to hold their valuable employees because these employees are imperative to their success. The compensation, work life balance, career development, relationship management and recognition are the factors affecting employee retention in IT companies. The results indicate that there is significant difference between socio-economic profile of employees and factors affecting employee retention in select IT companies in Bangalore City. Compensation, work life balance, career development, relationship management, and recognition are significantly influence on the employee retention.